Cognitive Function Analysis Using Telephone-Moca On Resident With Post Covid-19 Infection In Dr. Moewardi Hospital 2020-2021 - Befrie Mahaztra Sudarman; Rivan Danuaji (Magna Neurologica, 2023)
Introduction: Individuals after Covid-19 infection are suspected to have symptoms of cognitive impairment. Researchers wanted to use the telephone version of MoCA-22 assessment to assess cognitive function. Method: Cross-sectional study at Dr. Moewardi Hospital, Surakarta. Researchers assessed cognitive function telemedicine using Telephone-MoCA 22 and then compared it with the 30-point standard MoCA-INA examination. The analysis is continued on the results of inspection of each component. Results: During 2020-2021 there were 191 Residents who were infected with Covid-19. After screening, 69 people were able to complete the study, of which 34 people with a history of Covid-19 infection (49,2%) and 35 people (50,8%) without a history of Covid-19 infection. The subjects consisted of 34 men (49,2%); 35 women (50,8%); age range 25-33 (±28.97) years; Education grade is 28 juniors, 27 intermediate, and 17 seniors Resident. In the regression test, it was found that effect of Covid-19 history on cognitive function with p-value = 0,94 if using MoCA 30, and p-value = 1,17 if using T-MoCA 22. Comparative test of the two assessments obtained p-value = 0.475. In the analysis of each component obtained less than the maximum value on components of calculation, repetition and delayed memory. Conclusion: In the study, it was found that a history of Covid-19 infection had no effect on cognitive function in research subjects tested using MoCA-INA or Telephone-MoCA. T-MoCA examination has a test value that is not significantly different from the full version of MoCA 30 points.